Diseño de un filtro para el tratamiento de aguas de aljibe en la Vereda Sucre Occidental en Chiquinquirá. (2022)
This investigation was mainly based on the filtration technique as a unitary operation for the treatment of cistern water located on the Sucre Occidental mountain of the municipality of Chiquinquirá, Colombia because this rural area does not have a water supply network that guarantees a constant flow of drinking water safety and consumable. Throughout this document the generalities of the municipality under study are described, a review of the theoretical and technical foundations applicable to water treatment was carried out. An initial diagnosis of the research area was made and the quality of the cistern's water was characterized through standard methods for a physicochemical and microbiological analysis at the laboratory level where it was determined that the color was 25 UPC above the maximum parameter, the turbidity was 2.5 NTU above the limit, the residual chlorine concentration is zero, the total iron